Design and development of multipurpose educational and research platform (MERP) for learning advance control and IOT technologies - Muhammad Ali Akbar (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Vision TN50 “Transformasi Nasional 2050” of Malaysia is encouraging institutions to produce more talent for digital transformation of industries and enterprises. One of them is a new domain for Internet of Things (IoT) technologies where the students are required to develop their skills and knowledge in the field of advance control like industrial automation & robotics. Engineering platforms are the key component of engineering labs for teaching the programing and hardware concepts. The existing engineering labs having industrial standard PLC platform, but these platforms are lacking in term of advance control and IoT integration features. Few institutions are offering IoT and its being taught on the prototype scale controllers and microcomputers, which does not fulfil the design of industrial grade applications. In this research, a multipurpose educational and research platform (MERP) for learning advance control and IoT technologies was designed and developed. The MERP is purposely developed for technical institutions to teach and train the undergraduates and postgraduate students. The platform is divided into two parts; 1) the main panel and 2) the application panels (Motor control and Project board). This low-cost developed platform is using industrial standard controller which is suitable for industrial and enterprise applications prototyping. Three modules were designed to teach / train the students on this platform; 1) introduction to Industry 4.0 & IoT, 2) controller programming, configuration and machine to machine (M2M) communication, and 3) design and development of web and mobile application. The integration of MERP is done in engineering degree program at university level purposely to validate the impact of MERP in engineering education using survey. Based on results analysis, students had learnt to use this platform very effectively by developing a real time IoT application. The developed MERP and its contents meet the IoT layers to provide insight of this technology. In conclusion, the developed modules outcome is in-line with course objectives and IoT pillars to enhance student skills in industrial control technique. It is necessary to expose the student with the latest update of control technologies using this latest control platforms to meet industrial demand for marketable student in the future.